Crisis and Conflict in Agriculture - Zurayk, Rami (CAB International, 2018)
This book examines both how agriculture and rural issues can cause crisis and conflict, and what the effects of crisis and conflict, including violence and natural disasters, are on agriculture. Case studies examine a wide range of crises and conflicts, primarily in developing countries, and appropriate responses to mitigate their effects.